Computed Tomography Imaging Assessment of the Effect of Vancomycin Paste on Poststernotomy Healing - Basha MAA (Dove Medical Press, 2021)
Mohammad Abd Alkhalik Basha,1 Dina Said Shemais,2 Essam Saad Abdelwahed,2 Rabab Mahmoud Elfwakhry,1 Ayman Fathy Zeid,1 Ahmed A El-Hamid M Abdalla,1 Sameh Abdelaziz Aly,3 Dalia Said Abdelrahman,3 Anwar A Elshenawy,4 Waleed Mansour,5 Khaled Ahmed Ahmed Elbanna,6 Mohammad El Tahlawi,7 Nezar Elnahal2 1Department of Radiodiagnosis, Faculty of Human Medicine, Zagazig University, Zagazig, Egypt; 2Department of Cardiothoracic Surgery, Faculty of Human Medicine, Zagazig University, Zagazig, Egypt; 3Department of Radiodiagnosis, Faculty of Human Medicine, Benha University, Benha, Egypt; 4Department of Surgical Oncology, Faculty of Human Medicine, Aswan University, Aswan, Egypt; 5Department of Chest Medicine, Faculty of Human Medicine, Zagazig University, Zagazig, Egypt; 6Department of Internal Medicine, Faculty of Human Medicine, Zagazig University, Zagazig, Egypt; 7Department of Cardiology, Faculty of Human Medicine, Zagazig University, Zagazig, EgyptCorrespondence: Mohammad Abd Alkhalik BashaDepartment of Radiodiagnosis, Faculty of Human Medicine, Zagazig University, Zagazig, 44631, EgyptTel +20 1099098900Email Mohammad_basha76@yahoo.comPurpose: To assess vancomycin paste effect on poststernotomy healing in high-risk coronary artery bypass grafting (CABG) patients compared to bone wax using the 6-point computed tomography (CT) score. Additionally assessed the reliability of this score and its relationship to the occurrence of infection.Patients and Methods: A prospective comparative analysis included 126 high-risk CABG patients. The patients were randomly assigned into bone wax or vancomycin paste for sternal haemostasis. All patients were submitted to CT examinations 6-months postoperative. Two radiologists independently reviewed all CT scans to assess sternal healing using the 6-point CT score. The CT healing score of the two groups was compared. The kappa statistics were used to calculate the inter-reader agreement (IRA) of the 6-point CT score.Results: The final analysis included 61 patients in each group. The main CT score for sternal healing was 3.9± 0.4 in the vancomycin group and 3.3± 0.8 in the bone wax group. Patients in the vancomycin group had a higher statistically significant improvement in CT healing score than those in the bone wax group (p< 0.001). There was no statistically significant relationship (p = 0.79) between the occurrence of infection and the 6-point CT score in the vancomycin group. The overall IRA of the 6-point CT score was good in two groups (κ = 0.79 in the vancomycin group and = 0.78 in the bone wax group).Conclusion: Vancomycin paste had a better CT healing score and can be used as a sternal haemostatic material instead of bone wax. The 6-point CT healing score is a reliable diagnostic tool for evaluating sternal healing.Keywords: computed tomography, sternal healing, poststernotomy, vancomycin paste, CT